Health Care Charges Associated With Physical Inactivity, Overweight, and Obesity - Louise H. Anderson, MS; Brian C. Martinson, PhD; A. Lauren Crain, PhD; Nicolaas P. Pronk, PhD; Robin R. Whitebird, PhD; Lawrence J. Fine, MD, DrPH; Patrick J. O'Connor, MD, MPH (Centers for Disease Control and Prevention, 2005)
Introduction Physical inactivity, overweight, and obesity are associated with increased morbidity and mortality. The objective of this study was to estimate the proportion of total health care charges associated with physical inactivity, overweight, and obesity among U.S. populations aged 40 years and older. Methods A predictive model of health care charges was developed using data from a cohort of 8000 health plan members aged 40 and older. Model cells were defined by physical activity status, body mass index, age, sex, smoking status, and selected chronic diseases. Total health care charges were estimated by multiplying the percentage of the population in each cell by the predicted charges per cell. Counterfactual estimates were computed by reclassifying all individuals as physically active and of normal weight while leaving other characteristics unchanged. Charges associated with physical inactivity, overweight, and obesity were computed as the difference between current risk profile total charges and counterfactual total charges. National population percentage estimates were derived from the National Health Interview Survey; those estimates were multiplied by the predicted charges per cell from the health plan analysis. Results Physical inactivity, overweight, and obesity were associated with 23% (95% confidence interval [CI], 10%-34%) of health plan health care charges and 27% (95% CI, 10%-37%) of national health care charges. Although charges associated with these risk factors were highest for the oldest group (aged 65 years and older) and for individuals with chronic conditions, nearly half of aggregate charges were generated from the group aged 40 to 64 years without chronic disease. Conclusion Charges associated with physical inactivity, overweight, and obesity constitute a significant portion of total medical expenditures. The results underscore the importance of addressing these risk factors in all segments of the population.